Changes in income taxes in Poland in the opinion of small and medium enterprises - Jarczok-Guzy, Magdalena (Zmiany w podatkach dochodowych w Polsce w opinii małych i średnich przedsiębiorstw, 2019)
This article is a presentation of primary research conducted within the research potential of the Department of Public Finance of the University of Economics in Katowice entitled “Instruments of the state’s fiscal policy and the development of small and medium-sized enterprises.” The research goal of the work is to present the opinions of entrepreneurs on the most important post-shift changes introduced in Poland in 2017-2018. Fifty medium-sized enterprises in Poland with different activity profiles and territorial coverage comprised the research object. The methods of statistical analysis and deduction were used. As a result of the analysis, it turned out that the entrepreneurs’ enthusiasm for reforms was high. Entrepreneurs positively evaluated the new privileges and preferences, most of them also took advantage of the available privileges. The work also discusses the consecutively introduced changes in a concise manner
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 53-62
Keywords: income tax; legal changes; one-off depreciation write-off; podatek dochodowy; zmiany prawne; jednorazowy odpis amortyzacyjny